Kejadian Anemia pada Bayi Usia 6 Bulan yang Berhubungan dengan Sosial Ekonomi Keluarga dan Usia Pemberian Makanan Pendamping Asi - Siti Helmyati, Hamam Hadi, Wiryatun Lestariana (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: The high prevalence of iron deficiency among infant after six months of age, especially in developing country need to be aware because of their long-term consequences for the infant. Iron deficiency in infancy has been shown to delay cognitive and psychomotor development.Objective of the study: The study was conducted to assess the association between maternal hemoglobin concentration at 6 month postpartum, complementary breastfeeding and maternal socioeconomic status at 6 mo with infant hemoglobin concentration at 6 mo.Methods: The study was designed as a cross sectional study. Sample recruited in this study included women at six month postpartum who still breastfeed their baby. Mother’s hemoglobin concentration was analyzed using cyanmethemoglobin method and their infant’s haemoglobin by azidimethemoglobin with HemoCue tool.Results: This study showed that the prevalence of anemia among infants at 6 month of age was very high (75.32%). Complementary breastfeeding and socioeconomic status were associated with infant haemoglobin concentrationsConclusions: Although no significant association between maternal and infant anemia were identified, there was a tendency for anemic mother to have infant with lower haemoglobin concentration. A longitudinal study is needed to assess this association.Keywords: infant, lactating mother, hemoglobin status, socioeconomic status, complementary breastfeeding